Answer:
The roots of equations are as m =
And n =
Explanation:
The given quadratic equation is 2 x² + 6 x - 1 = 0
This equation is in form of a x² + b x + c = 0
Let the roots of the equation are ( m , n )
Now , sum of roots =
![( - b)/(a)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ofdqoyxxo01im10s9qsnwgx6fn5dpyawim.png)
And products of roots =
![(c)/(a)](https://img.qammunity.org/2020/formulas/mathematics/college/69ybkxx8b8wwgkxz2fg6y3hiz0yya71vcs.png)
So, m + n =
= - 3
And m × n =
![( - 1)/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/db5r8hgjeqjtbtz1zrj68rewvy68i2zmix.png)
Or, (m - n)² = (m + n)² - 4mn
Or, (m - n)² = (-3)² - 4 (
)
Or, (m - n)² = 9 + 2 = 11
I.e m - n =
![√(11)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/5ahtvvxquy6szz3nle20j50dop4m79ka6e.png)
Again m + n = - 3 And m - n =
![√(11)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/5ahtvvxquy6szz3nle20j50dop4m79ka6e.png)
Solving this two equation
(m + n) + ( m - n) = - 3 +
![√(11)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/5ahtvvxquy6szz3nle20j50dop4m79ka6e.png)
I.e 2 m = - 3 +
![√(11)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/5ahtvvxquy6szz3nle20j50dop4m79ka6e.png)
Or, m =
![(-3)/(2) + (√(11) )/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/p076uuctt8xrm0lvychlmcg4h6jdjf6wsu.png)
Similarly n =
Hence the roots of equations are as m =
And n =
Answer